EVALUASI POSTUR KERJA OPERATOR PACKING BERBASIS PENDEKATAN RAPID ENTIRE BODY ASSESMENT DI UD. XEVIPRODUCTION - Dimas Aditya Ferdiansyah; Nina Aini Mahbubah (SIGMA TEKNIKA, 2022)
UD. XeviProduction is a home industry in snacks that has a high dependence on human labor activities. The pressing process results in excessive fatigue so that the performance on the job is not optimal. This fatigue condition causes musculoskeletal muscle disorders in pressing operators. This study aims to evaluate work postures that affect operators and recommendations for work aids to minimize complaints due to improper work postures on press sealer machine operators. Nordic Body Map (NBM), Rapid Entire Body Assessment (REBA), and Anthropometry are ergonomic approaches used in research. NBM is used to distinguish pain from the neck to the feet. The REBA method is used to analyze body posture. The anthropometric method is used to make a product whose size is adjusted by human body posture. The results of the NBM identification revealed that the neck pain, the back was very sore, the waist was very sore, the hip hurt, the left thigh hurt, and the right thigh hurt. Posture analysis of UD pressing workers. In addition, based on the REBA calculation result, distinguish a risk score of 8, which is high. The tool designed is an ergonomic chair. After the tool has been made, the risk of workers decreases to a score of 2, which is low